SOCS1, SOCS3, and PIAS1 Promote Myogenic Differentiation by Inhibiting the Leukemia Inhibitory Factor-Induced JAK1/STAT1/STAT3 Pathway - Yarui Diao; Xi Wang; Zhenguo Wu (2009)
We recently showed that a leukemia inhibitory factor (LIF)-engaged signaling pathway consisting of JAK1, STAT1, and STAT3 plays dual roles in myogenic differentiation: while it participates in myoblast proliferation, it also actively represses differentiation. Downregulation of this pathway is required at the onset of differentiation. However, it remained unclear how this is achieved mechanistically. We now show that SOCS1, SOCS3, and PIAS1 promote myogenic differentiation by specifically inhibiting the LIF-induced JAK1/STAT1/STAT3 pathway via distinct targets; whereas SOCS1 and SOCS3 selectively bind and inhibit JAK1 and gp130, respectively, PIAS1 targets mainly the activated STAT1 and prevents its binding to DNA. We further demonstrated that the SUMO E3-ligase activity of PIAS1 is dispensable for its role in myogenic differentiation. Collectively, our current study revealed a molecular mechanism that explains how the LIF-induced JAK1/STAT1/STAT3 pathway is downregulated upon myogenic differentiation.